Everyday geographies of family: feminist approaches and interdisciplinary conversations. Issue 5 (3rd May 2020) - Tarrant, Anna; Hall, Sarah Marie
Abstract: Our key aim with this collection, a combination of original empirical contributions and interventions by experts from across social geography and sociology, is to consolidate and advance feminist, interdisciplinary approaches to the everyday geographies of family via contemporary, empirically grounded research and direct interdisciplinary exchanges. This themed section showcases cutting edge geographical work in relation to the everyday geographies of family life; highlights the diversity of work being done within feminist geography and; develops a feminist geography that is enriched through engagement with interdisciplinary intellectual exchanges. We describe the intervention section that follows this introductory piece, bringing together writing from across sociology and geography, where there has been a cross-pollination of ideas around everyday family life, but very little concerted effort to bring these into dialogue to date. In introducing each contributor and their substantive interests, we will draw out relevant theoretical links across papers that illustrate how both family and the everyday, as key concepts, are being unsettled and problematised. Contributors to the intervention section are notable scholars that have set and shaped key agendas and debates. In their shorter papers, they will reflect on their influence on developing debates about family and everyday life. Drawing links across this suite of themed and intervention papers, it will be argued that interdisciplinary work around the family is important for carving out and consolidating feminist, interdisciplinary discussions and for determining what might also be distinctive about feminist approaches to family geographies as debates progress.